A Virtual Reality Exergame with a Low-cost 3D Motion Tracking for At-Home Post-Stroke Rehabilitation - Tannus de Souza, Julia; Valentini, Caroline; Naves, Eduardo Lazaro Martins; Lamounier Jr., Edgard Afonso (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
Stroke is one of the main causes of long-term disability worldwide. Conventional upper limb physiotherapy can be tedious, expensive and require physical transportation. Virtual Reality (VR) video games can help solve these problems. In fact, recent studies show that health professionals are increasingly interested in using VR games for post-stroke rehabilitation. However, commercial possibilities can be inaccessible, in terms of time, space and cost, and also inadequate to the needs of patients and therapists. Thus, in this work, a VR video game with an innovative alternative for tracking the 3D movement of the upper limb is proposed. As a result, a system that uses optical capture with a regular camera and colored sphere markers, while maintaining lightweight real-time processing on mobile devices was done. The fact that the controller can be handcrafted by the users makes the game very low-cost, possible to be distributed worldwide, reaching a large number of people, and possible to be played and monitored remotely. This new form of motion capture can make the VR exergame interaction more intuitive, therefore increasing the user's immersion in his therapy exercises. The proposed system was tested in order to find out how accurate it can be, compared to a gold standard system (a goniometer). It has been found that the system has limitations, such as low accuracy in obtuse angles and camera distortions. Still, it seems promising, due to its accessibility, very low cost, customization to the needs of patients and therapists and good tests results, as a complementary alternative for VR post-stroke rehabilitation.